Effectiveness of dental sealant in preventing dental caries among students in a school dental health program of Pranangklao hospital, Nonthaburi - Plengsringam, Nuchanart; Tharasombat, Soison (Journal of Health Science of Thailand, 2017)
The objective of this study was to assess the effectiveness of dental sealant of first permanent molars in preventing caries. The samples were the first permanent molars of grade 6 students in 2011 in 19 schools under the Office of Basic Education Commission and local administrations organizations, and under the dental health coverage of Pranangklao Hospital, Nonthaburi province. Eligible students were those who received dental health service since grade 1 of whom many received sealant service covering their first molars. Chi-square and odds ratio were used as statistical tools to analyze the data. It was found that there were 1,795 molar samples of 473 students that fit with the inclusion criteria. Percentage of dental caries was found to be significantly lower among the sealed molars compared to the unsealed ones (p<0.05). The findings were also true for both left and right lower molars. Therefore, the sealant program has been found to be effective in reducing the incidents of dental caries in primary school students, particularly for the lower molars.